Comparison of Dexmedetomidine or clonidine as adjuvant to Preemptive Thoracic Epidural Ropivacaine analgesia with propofol based TIVA in fast-track thoracic anaesthesia for open thoracic surgeries (Indian Journal of Applied-Basic Medical Sciences, 2021)
BACKGROUND: –Thoracic surgeries are very painful, I which require adequate anaesthesia& analgesia to modulate physiological responses of pain. In present study pre-emptive use of placebo/Dexmedetomidine / clonidine with Ropivacaine based perioperative thoracic epidural analgesia.AIM & OBJECTIVES: –To use both Alpha agonists with Ropivacaine for perioperative epidural analgesia with TIVA by propofol assessment of perioperative oxygenation, awareness, total dose of propofol, fast-tracking criteria were measured.STUDY DESIGN:A randomised retrospective observational studyMETHODS:In present study 75 adult patients of ASA grade, I/II of various elective thoracic surgeries in department of cardiothoracic & vascular surgery at V.S General hospital, NHLM Medical College, Ahmedabad, Gujarat.OBSERVATIONS AND RESULTS: -Both Alpha agonists with Ropivacaine provide good RESULTS: – bolus propofol & fentanyl required to maintain BIS in comparison to Ropivacaine alone.Fast-tracking criteria were comparable & good in each Group.CONCLUSION-Thoracic epidural analgesia with Ropivacaine definitely improved recovery, & provide good Fast-tracking criteria. Thoracic epidural Dexmedetomidine or clonidine with Ropivacaine provides better perioperative analgesia and improve Postoperative analgesia than Ropivacaine alone.
Keywords: Preemptive Thoracic epidural Ropivacaine; Dexmedetomidine; Clonidine; TIVA; One lungAnaesthesia; Open thoracic surgery